The Impact of KOSICA Media (Light Properties Box) on the Learning Interest of Grade IV Students in Light Properties Materials - Maimunah, Khairun Nisa; Abdullah, Kusmajid (Elementary Teacher Education Program, Majalengka University, 2024)
The low interest in learning science on the properties of light is the background for this research due to the use of less relevant learning media. This research aims to find out how fourth grade students' interest in learning about the properties of light is influenced by KOSICA media. This research uses an experimental approach in quantitative research with a nonequivalent control design. The sample used was 64 class IV students. Data collection techniques include a learning interest questionnaire and a KOSICA media questionnaire. Obtaining final score research data shows that the experimental group got a score of 70.44 and the control group got a score of 63.13. It can be seen that the final score of the experimental group was 70.44 > 63.13 greater than the control group. Because KOSICA media can make learning more meaningful and enjoyable, make students more active in learning and can arouse students' interest in learning, it has been proven that the use of this media can influence the enthusiasm of fourth grade students in studying the properties of light.